Nematode control on plantain suckers (Musa spp. Aab genome) through submergence in boiling water: emergence rates, early growth, bunch yield and root health - Hauser, S.; Messiga, F.N.K. (International Society for Horticultural Science, 2010)
Plantain (Musa spp. AAB genome) is an important staple of the humid zoneof West and Central Africa. Root nematodes, specifically Radopholus similis, alongwith other pests and diseases are a major cause of yield loss. Farmers are unawareof the presence, symptoms and effects of nematodes. No commonly used method toclean infested plantain suckers exists. This paper presents a simple, inexpensive andhighly mobile method to treat plantain suckers against pests and diseases attached tothe suckers. The purpose of the paper is primarily to show that submerging plantainsuckers in boiling water for a limited time (<60 s) does not compromise emergenceand crop establishment and has the potential to significantly increase plantainyields. Submerging suckers with a corm circumference of at least 20 cm in boilingwater for 0 to 60 s had no significant effect on the rate of emergence and cropestablishment. Exposure times between 20 and 40 s appear to be most suitable toattain high crop establishment rates. After sucker submergence in boiling water for30 s, no living nematodes were found in corm surface tissue. Yield response toboiling water treatment was positive (P<0.001) with a fresh bunch yield increasefrom 3.99 (untreated control) to 11.88 t/ha (boiling water treated). The techniquerequires very little capital investment (<$10) and only marginal additional labor. Itappears suitable as a general technique to reduce both specific and unspecific pestsand diseases spread by conventional suckers.